Menanamkan Karater Sopan Santun Mulai Dini Kepada Anak-Anak Oleh Mahasiswa PKL FISIP USU - Bengkel Ginting; Ardiansyah Sinaga (Yayasan Literasi Sains Indonesia, 2022)
The author did practicum I at the AMAL Foundation/Social Washliyah Orphanage. The first practicum carried out by the author was to examine the problems experienced by orphans. After the emergence of the Covid-19 outbreak in Indonesia starting in early March 2020, which has begun to subside, it is currently having a significant impact on various aspects of Indonesian people's lives. Not only on the economic, health, work aspects, but also on the norms of decency and politeness of children. The current era is facing the covid 19 pandemic and the new normal era, many millennial parents do not realize the importance of speaking and speaking well when in front of children when staying at home. In fact, providing examples of good language and speaking ethics can increase the value of a child's self-decency. From this problem, the writer is interested and has a goal to improve the character of good manners in children. This time, PKL 1 was carried out using the casework method through a general intervention stage consisting of Engagement Intake Contract, Assessment, Planning, Intervention, Evaluation, and Termination. After doing all the casework stages, the results are faced by the author so that the orphans continue to apply the values ​​of courtesy wherever they are.